Dengue Fever Responses in Dhaka City, Bangladesh: A Cross-Sectional Survey - Rahman, Md. Mostafizur; Islam, Abu Reza Md. Towfiqul; Khan, Saadmaan Jubayer; Tanni, Kamrun Nahar; Roy, Tuly; Islam, Md. Rakibul; Rumi, Md. Alim Al Raji; Sakib, Mohammed Sadman; Abdul Quader, Masrur; Bhuiyan, Nafee-Ul-Islam; Chisty, Musabber Ali; Rahman, Farzana; et al. (International Journal of Public Health, 2022)
Abstract Objectives: This study intends to evaluate the Dhaka city residents' individual views towards DF. Methods: A cross-sectional survey was conducted during the COVID-19 pandemic. The pre-tested KAP survey used google forms for collecting data from individuals. Kruskal-Wallis or Mann-Whitney U test was carried out, where appropriate, while logistic regression models were performed to determine the predictors of KAP level. Results: 1008 individuals participated in a pre-tested KAP survey. More than 20% reported being affected by DF before the survey, where the majority of them rated their current place as being moderately safe (43%). In terms of DF control, 65% of residents had good knowledge, and 68% reported good practice for ,whereas they demonstrated an overall good attitude. Female residents demonstrated better DF attitudes (OR: 0.69; P<0.05) and practices (OR: 0.66; P<0.01) compared to the male. The mixed unit residents had poor KAP levels. Educational attainment can also play an essential role in enhancing the attitude level Conclusions: Overall, dengue surveillance activities with enough campaigns are required to bring a behavioral change among the Dhaka city residents.